TECHNOLOGY OF OBTAINING "SMART" MATERIALS BY ADDING FIBER FILLERS BASED ON THERMOPLASTIC POLYMERS - Urishev Gulyam; Otaboyeva Gulmira Komolidin qizi; Qorachayeva Oltinoy Akbaraliyevna (International Journal of Innovations in Engineering Research and Technology, 2021)
This article provides information about fiber fillers, methods of obtaining composite materials, properties, targiibi, properties, use, innovations of "smart" materials. The results of the studies on the changes in the polymer composition of fiber and other fillers are given.